CD301b+ dendritic cells suppress T follicular helper cells and antibody responses to protein antigens - Yosuke Kumamoto; Toshiro Hirai; Patrick W Wong; Daniel H Kaplan; Akiko Iwasaki (eLife, 2016)
Strong antibody response is considered a hallmark of a successful vaccine. While dendritic cells (DCs) are important for T follicular helper (Tfh) cell priming, how this process is regulated in vivo is unclear. We show here that the depletion of CD301b+ DCs specifically enhanced the development of Tfh cells, germinal center B cells and antibody responses against protein antigens. Exaggerated antibody responses in mice depleted of CD301b+ DCs occurred in the absence of any adjuvants, and resulting antibodies had broader specificity and higher affinity to the immunogen. CD301b+ DCs express high levels of PD-1 ligands, PD-L1 and PD-L2. Blocking PD-1 or PD-L1 during priming in wild-type mice partially mimicked the phenotype of CD301b+ DC-depleted animals, suggesting their role in Tfh suppression. Transient depletion of CD301b+ DC results in the generation of autoreactive IgG responses. These results revealed a novel regulatory mechanism and a key role of CD301b+ DCs in blocking autoantibody generation.